Comparison of signal compression efficiency using Fourier transform and wavelet transform - Давлет’янц, А. О. (Proceedings of National Aviation University (archive), 2021)
Experimental data for estimating the efficiency of signal compression using Fourier transforms and wavelet transforms are presented. It is shown that wavelet transform is more expedient for processing nonstationary, broadband signals, and in the case of accumulation of most of the energy of the signal in a small number of spectral components, the Fourier transform is more efficient.